Relationship between cathepsins and cardiovascular diseases: a Mendelian randomized study - Qiaoqiao Li; Zhongzheng Zhou; Teng Xu; Xueping Gao; Yake Lou; Zijun Chen; Muzi Zhang; Qinghua Fang; Jie Tan; Jing Huang (Frontiers Media S.A., 2024)
Background: Cardiovascular diseases (CVDs) are the leading age-related disorders worldwide, with their prevalence increasing annually. Cathepsins are protein-degrading enzymes essential for processes such as intracellular protein breakdown, apoptosis, and immune responses. Recent studies suggest a potential link between cathepsins and CVDs, yet the exact causal relationship remains to be elucidated. To address this, we propose using Mendelian randomization (MR) to explore the causal relationships between cathepsins and CVDs.Methods: We obtained single nucleotide polymorphism (SNP) data for cathepsins from the INTERVAL study, a publicly accessible genome-wide association study (GWAS) dataset. Outcome SNP data were sourced from seven distinct GWAS datasets, ensuring a comprehensive analysis across multiple cardiovascular outcomes. For MR analysis, we primarily employed the inverse variance weighted (IVW) method, known for its efficiency when all SNPs are valid instruments. This was supplemented by the weighted median and MR-Egger methods to provide robustness against potential violations of MR assumptions, such as pleiotropy. The IVW method offers precision and efficiency, the weighted median method adds robustness against invalid instruments, and the MR-Egger method helps identify and correct for pleiotropic biases. Cochran's Q test was utilized to assess heterogeneity, and sensitivity analyses were conducted using MR-PRESSO and the leave-one-out approach.Results: The strength of the associations between exposure and outcome was measured using odds ratios (ORs), and results were presented with 95% confidence intervals (CIs). The cathepsin E increases the risk of myocardial infarction (MI) (OR = 1.053%, 95% CI: 1.007-1.101, p = 0.024) and ischemic stroke (IS) (OR = 1.06%, 95% CI: 1.019-1.103, p = 0.004). Conversely, cathepsin L2 decreases the risk of chronic heart failure (CHF) (OR = 0.922%, 95% CI: 0.859-0.99, p = 0.025) and atrial fibrillation (AF) (OR = 0.956%, 95% CI: 0.918-0.996, p = 0.033). Cathepsin O was associated with an increased risk of IS (OR = 1.054%, 95% CI: 1.008-1.102, p = 0.021) and AF (OR = 1.058%, 95% CI: 1.02-1.098, p = 0.002).Conclusion: Our MR analysis reveals that cathepsin E is a risk factor for MI and IS, cathepsin L2 offers protective effects against CHF and AF, and cathepsin O increases the risk for IS and AF.